P-EGS09 The Introduction of an Ambulatory Surgical Pathway. (16th December 2021) - Wall, Joshua; Boag, Katie; Kowal, Mikolaj; Plotkin, Tobias; Maguire, Rachel; Peckham-Cooper, Adam
Abstract: Background: Since the publication of the Emergency General Surgery Commissioning Guide by ASGBI in 2014, there has been a drive to develop ambulatory pathways for acute surgical patients, saving inpatient stays and reducing the risk of hospital-acquired infections. Many units, like ours, had a large workload increased by seeing next day returns as well as acute presentations. In October 2020 an Institute of Emergency General Surgery was formed who developed an ambulatory pathway to ameliorate some of these issues and provide a point of contact for primary care referrals, for one the busiest emergency general surgical takes in the UK. Methods: A retrospective analysis was undertaken to identify all acute referrals to general surgery over a 14-day period in February 2019 prior to (Pre-ASC) and 2021 after (Post-ASC) the introduction of an Ambulatory Surgical Clinic (ASC). All patient episodes were reviewed, and descriptive statistics on overall attendance to the surgical assessment unit (SAU), admissions to inpatient wards and referrals to ASC were analysed. Patients presenting to the acute urology take were used as a control to compare the number patients attending the surgical assessment unit both before and during the COVID-19 pandemic. Results: 830 patients presented over the 28-day study period (426 pre-ACS vs 404 post-ACS; 5% reduction), totalling 992 patient encounters including planned returns (525 vs 467; 11% reduction). After the introduction of the ASC total attendance to SAU was reduced by 42% (525 vs 306); next day return attendances were reduced by 87% (99 vs 13) and attendances from primary care were reduced by 68% (208 vs 67). The proportion of patients admitted was similar (46% vs 50%). 146 patients attended the ASC, and 15 patients received telephone advice alone. The control group saw attendance increase by 25% (178 vs 223). Conclusions: The results clearly show that the introduction of the ASC has decreased attendance to SAU, freeing clinicians to dedicate more time to those acutely unwell. The similar proportion of admissions after the introduction of the ASC suggests that the ambulatory pathway correctly identifies those who are well enough to be managed as outpatients. The increased attendance in the control group suggests that the data were not the results of a decrease in referrals due to COVID-19. The results shared here should encourage other large units to consider developing ambulatory pathways.